Curcumin enhances liver SIRT3 expression in the rat model of cirrhosis - Sara Chenari (Iranian Journal of Basic Medical Sciences, 2017)
Objective(s): Bill duct ligation (BDL) is a representative model of biliary cholestasis in animals. Curcumin has a protective effect on the liver; however, its underlying mechanisms are not completely known. This study explored the hepatoprotective activity of curcumin on hepatic damage via measuring the expression of sirtuin3 (SIRT3), AMP-activated protein kinase (AMPK), carnitine palmitoyltransferase 1A (CPT-1A), isocitrate dehydrogenase2 (IDH2) and manganese superoxide dismutase (MnSOD) as well as the level of serum lipid profile in the BDL fibrotic rat model. Materials and Methods: The study consisted of four groups (n=8 for each of Wistar rats): sham group, sham+curcumin (sham+Cur) group (received curcumin 100 mg/kg/day), BDL+Cur group, and BDL group. Transcription levels of SIRT3, AMPK, CPT-1A, IDH2, MnSOD and protein expression level of SIRT3 were measured by real-time PCR and Western blotting, respectively. Results: It was identified that SIRT3, AMPK, CPT-1A, IDH2 and MnSOD expression significantly decreased in BDL rats compared to sham rats; however, in the curcumin treatment of BDL rats, the expression of these factors increased significantly compared to BDL (P-value